A Comparative Study to Assess the Effectiveness of Alalekaayi Water Rinse Versus Lukewarm Water Rinse on Leucorrhea Among Reproductive Age Women Working in A Selected Institutions at Namakkal District - Sathiabhama, Sathiabhama; Punitha, P.; Bharathi, V.; Sathya, M.; Sivaranjani, S. (Journal of Neonatal Surgery, 2025)
Leucorrhea, commonly referred to as vaginal discharge, is a physiological phenomenon in women of reproductive age. It usually consists of whitish or yellowish discharge from the vagina, resulting from increased secretions by the vaginal and endocervical glands. The aim of this study is to compare the effectiveness of the selected symptoms of leucorrhoea among reproductive age women in experimental group I and experimental group II, To evaluate the effectiveness of Alalekaayi water wash and Lukewarm water wash by comparing pre-test and post-test score on leucorrhoea among women in experimental group I and experimental group II and To compare the effectiveness of Alalekaayi water wash and Lukewarm water wash on leucorrhoea among women in experimental group I and experimental group II in a selected institutions at Namakkal district. A qualitative approach with quasi experimental design was adopted for the present study. The samples selected for the study were 40 by using non probability purposive sampling technique in which 30 were selected for Experimental group I and 30 for Experimental group II. Data was collected by using structured interview questionnaire to assess the symptoms of leucorrhoea. The significant finding was assessed by using test retest method. Correlation coefficient value of reliability is 0.98. The results shows that, Experimental group I pre test mean value is 5.47 and post test mean value is 1.56, and Experimental group II pre test mean value is 5.63 and post test value is 4.28. There was more effectiveness in Color of vaginal discharge, Consistency of Vaginal discharge, Odour, Vaginal itching, Vaginal Burning Sensation, Quantity and Lower back pain by using Alalekaayi water wash (experimental group I) t=17.39 p<0.00001***DF=29 which is Highly Significant, in Lukewarm water wash (experimental group II) t= 2.89 p<0.00001***DF=29 which is Significant. By these interventions, we can provide the relevant information to the subjects and clearing up the misconceptions and they can understand locally available Alalekaayi water wash on leucorrhoea is the best possible treatment option among reproductive age women.